SA-17 Treatment of Coxofemoral Luxation Using Toggling Technique in Dog - A A N G D Wisesa; I W Y Semarariana; P S Dwipartha; P T E Sucitrayani; M P A Yunikawati; A A N O Pujawan; I N Suartha (Hemera Zoa, 2018)
Coxofemoral luxation occur because the femoral head and the acetabulum are separated (Mark, 2011). In small animals, coxofemoral luxation with craniodorsal position is the most common type of luxation that occur in dog (Ali, 2014). Arun et al. (2012), explain that coxofemoral luxation occurs due to neoplasia or serious trauma.There are several methods to solve this coxofemoral luxation such as non-surgical reduction, surgical reduction, femoral head and neck ostectomy (FHO), and total hip replacement. In this study, it was evaluated using surgical reduction with toggling technique in treatment of craniodorsal coxofemoral luxation in dog which appears to be technically easy, quick and has a good result.